Dampak Kualitas Layanan dan Kualitas Produk Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah PT Asuransi Jiwa BCA Life di Provinsi Jambi - Bella Maysi Putri; Ade Octavia; Andang Fazri (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study employs a quantitative approach with the aim of analyzing the influence of service quality and product quality on customer loyalty, with customer satisfaction serving as the intervening variable. The study was conducted among customers of PT Asuransi Jiwa BCA Life in Jambi Province. The independent variables in this study include service quality and product quality; the dependent variable is customer loyalty; and customer satisfaction acts as the intervening variable. Data collection was conducted by distributing questionnaires to customers who served as research respondents. The questionnaire was designed using a Likert scale to measure respondents’ perceptions of each indicator for service quality, product quality, customer satisfaction, and customer loyalty. The data obtained are primary data collected directly from the respondents. Data analysis was performed using the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method with the SmartPLS software. The analysis stages included testing the outer model to assess the validity and reliability of the research instruments, as well as testing the inner model to analyze the relationships between variables and test the research hypotheses. A test of the mediating effect of customer satisfaction was conducted to determine its role in mediating the influence of service quality and product quality on customer loyalty.